Relaciones entre la psicología clínica, la psicoterapia y la psicología de la salud (2013)
ABSTRACT: This article highlights a conceptualization of clinical psychology given its difference with Health psychology and the role it plays inside to psychotherapy. This definition will allow psychologists (clinical or health) to base their practice on other disciplines also concerned about the health and physical or mental illness.